Influence of Emulsion Components on Physicochemical Properties and Release of the Volatile Flavor Compounds from Orange Beverage Emulsion - Mirhosseini, Seyed Hamed (2007)
In the present study, the effect of main important factors affecting the headspace (HS) extraction efficiency of orange flavor compounds was investigated for the development of the solid phase microextraction (SPME) technique. The optimum HS-SPME conditions were established by using the diluted emulsion (1:100) including 15% NaCl, a 75 μm CAR/PDMS fiber at 45 °C for 15 min under stirring mode. Subsequently, the influence of different concentration levels of main beverage emulsion components namely Arabic gum (7-20% w/w), xanthan gum (0.1-0.5% w/w) and orange oil (6-14% w/w) on the physicochemical properties and release pattern of target volatile flavor compounds from orange beverage emulsion was studied using a three-factor central composite design (CCD). The main objective of this study was to determine the optimum level of the main emulsion components which led to the desirable response goals. The desirable response goals include: (1) the highest emulsion stability, viscosity, pseudoplastic behavior, turbidity, cloudiness, electrophoretic mobility and largest magnitude of ζ-potential; (2) the least turbidity loss rate, conductivity, size index, average droplet size, polydispersity index, pH and flavor release content; and (3) the target value for density. The results indicated that the physicochemical properties of emulsion and release behavior of target volatile flavor compounds from orange beverage emulsion were significantly (p < 0.05) influenced by the main and interaction effects of the main beverage emulsion components. In most cases, the significant (p < 0.05) nonlinear regression models were fitted by the response surface analysis for describing the variation of physicochemical properties of emulsion. The response surface models exhibited high R2 values (> 0.8) which had no indication of significant (p > 0.05) lack of fit in most cases, thus ensuring a satisfactory adjustment of the polynomial regression models fitted to the experimental data. The fitted models were accurately explained by the high variation of physicochemical properties of emulsion as a function of the proportion of main beverage emulsion components. In general, the predicted optimum for the orange beverage emulsion was 20% (w/w) Arabic gum, 0.3% (w/w) xanthan gum and 14% (w/w) orange oil. The results also indicated that CCD was found to be a very useful experimental design for investigating the variation of physicochemical properties of orange beverage emulsion and optimizing the proportion of beverage emulsion components leading to the desirable orange beverage emulsion. The results exhibited that independent variables had the least and most significant (p < 0.05) effects on the release of β-pinene and γ-terpinene, respectively. The effect of hydrocolloid concentration on volatile compound release was more pronounced with the negative effect of xanthan gum concentration on the overall release content. In the present study, the reduction in flavor release intensity may be explained by the different phenomena such as adsorption, complexation, entrapment, hydrogen bonds and encapsulation of target flavor compounds induced by their interactions with Arabic gum, xanthan gum and other matrix constituents. Consequently, the effect of different concentrations of pectin (1.5, 3 and 4.5% w/w), carboxymethyl cellulose (CMC) (0.1, 0.3 and 0.5% w/w), glycerol (0.5, 1 and 1.5% w/w) and vegetable oil (2, 3 and 4% w/w) on the emulsion properties of the optimum beverage emulsion was investigated. The results indicated that these supplementary emulsion components (especially vegetable oil and pectin) could be used to modulate the physicochemical properties and release pattern of volatile flavor compounds from the orange beverage emulsion.